Pelatihan Peningkatan Produktivitas Pelaku Industri Rumahan melalui Teknologi Informasi dan Komunikasi di Kota Balikpapan - Tegar Palyus Fiqar; Ariyadi Ariyadi; Aditya Putra Pratama; Gusti Ahmad Fanshuri; Soleh Ardiansyah; Lovinta Happy Atrinawati; Sri Rahayu Natasia; Vinda Daningrum; Yuyun Tri Wiranti; Muhammad Ihsan Alfani Putera (Universitas Mathla'ul Anwar Banten, 2020)
TRAINING IN INCREASING PRODUCTIVITY OF HOME INDUSTRY BUSINESS OWNERS THROUGH INFORMATION AND COMMUNICATION TECHNOLOGY IN THE CITY OF BALIKPAPAN. Information and Communication Technology (ICT) could be effective tools for females to scale their small and medium enterprises. However, their role in ICT development is considerably minor. Men are still holding important role in ICT. On the other hand, women are dominated minor parts, such as administration, data entry, and komputer operation. In another word, ICT is measurably far out for women. Therefore, in order to scale home industries which are run by females, skill enhancements are needed in operating ICT for improving economist productivity. Indonesian Association of Higher Education in Informatics and Computing (APTIKOM) and Ministry of Female Empowerment and Child Protection (KPPPA) collaborate to organize ICT training for home industries by trained APTIKOM members. Kalimantan Institute of Technology (ITK) has chosen to prosvide training at Komputer Laboratory, ITK Campus. This program was held in order to give insight and knowledge on managing home industry with optimum effort by utilizing ICT.